Особливості процесу адаптації випускників інтернатного закладу системи освіти до соціального середовища - Гордієнко, Наталія Миколаївна; Гордиенко, Наталья Николаевна; Hordiienko, Nataliia M. (My University, 2016)
Для України актуальною проблемою залишається соціальна адаптація молоді до суспільно-політичного, професійно-трудового, сімейно-побутового й культурно-дозвіллєвого життя. Згідно з результатами порівняльного соціологічного дослідження життєвих планів випускників інтернатних закладів й осіб, котрі не навчалися в інтернатних закладах, зафіксовано вповільненість процесу адаптації випускників інтернатних закладів до соціального середовища, більш тривалий період освоєння соціального та життєвого простору, порівняно з людьми, які не навчалися в інтернатному закладі. Установлено, що в усіх вікових групах випускники інтернату меншою мірою готові займатися трудовою діяльністю, ніж інші громадяни. У віці понад 30 років проблема створення сім’ї все ще цікавить 17 % випускників інтернатів, тоді як серед іншого населення цього віку – 10 %. У зрілому віці менша частина випускників інтернатів, порівняно з іншими респондентами, розвʼязує проблему житла. The author analyzes the special characteristics of social integration of boarding school graduates into society. On the basis of analysis of scientific literature it was ascertained that social adaptation is a complex phenomenon which is extensively investigated from the perspective of modern sociology, philosophy, social psychology and social pedagogy. The actual problem for Ukraine is the problem of social integration of youth into socio-political, professional, cultural and family life. The article presents the results of sociological study of life plans of boarding school graduates and graduates of general education establishments. Data about future professional and social activities, further education, marriage, health care and home improvement were collected by using interviewing methods. The study finds that graduates of boarding schools demonstrate the lower ability to adapt to the social living conditions than graduates of general education establishments. It was found out that in all age groups boarding school graduates are less inclined to take up labouring than other citizens. Already among the graduates of 20–24 years old there are 18% less of those intending to take a job than in the control group (67 and 85 % respectively). By 30 years old, most graduates have finished their studies. Among the boarding school graduates, 20 % of 30–35-year-olds and 22 % of 26–44-year-olds are just planning to start a family, whereas in the control group the respective rate is 6–7 %. That means it takes a longer time by boarding school graduates to start a family. Boarding school graduates are less attentive to their own health than other citizens, which is true for all age groups except of the oldest – those above 45 years old. In this age group, the part of the graduates preoccupied with their health state is larger (32 and 25 %). Among seniors a smaller part of the graduates, when compared to other respondents, finds solutions to accommodation problems. Among those above 30 years old, family starting is a topical issue for 17 % of the graduates, whereas for other citizens the rate is 10 %.
Special Characteristics of Social Adaptation of Boarding School Graduates into Society
Keywords: соціальна адаптація; соціальна мобільність; інтернатний заклад; життєві плани; social adaptation; social mobility; boarding school; life plans